Correlation of Creatine Kinase Levels with Clinical Features and Survival in Amyotrophic Lateral Sclerosis - Tai, Hongfei; Cui, Liying; Guan, Yuzhou; Liu, Mingsheng; Li, Xiaoguang; Shen, Dongchao; Li, Dawei; Cui, Bo; Fang, Jia; Ding, Qingyun; Zhang, Kang; Liu, Shuangwu (Frontiers in Neurology, 2017)
Objective: To evaluate serum creatine kinase (CK) levels of amyotrophic lateral sclerosis (ALS) patients and to explore the relationship between CK levels and the clinical characteristics and survival prognosis of ALS patients. Methods: We analyzed the CK levels of 185 ALS patients who underwent long-term follow-up. The relationship between CK levels and clinical features including sex, age, disease duration, site of onset, body mass index, serum creatinine and spontaneous electromyographic activity were analyzed by univariate analysis and multiple linear regression. Kaplan–Meier and Cox proportional hazards models were used to explore whether CK levels were independently correlated with survival prognosis of ALS. Results: Baseline serum CK was raised in 43% of participants. The median CK level was 160 U/L (range: 20-2574U/L), and 99% of patients had a baseline serum CK level less than 1000 U/L. CK levels were significantly higher in male patients than in female patients (204 (169) U/L vs. 117 (111) U/L, P<0.001) and in patients with limb onset ALS than with bulbar onset ALS (P<0.001). CK levels were also correlated with serum creatinine (p=0.011) and the spontaneous potential score of electromyography (p=0.037) but not correlated with age (p=0.883), disease duration (p=0.116) or body mass index (p=0.481). Log CK was independently correlated with survival of ALS patients (HR=0.457, 95% CI 0.221-0.947, p=0.035) after adjusting for age, sex, site of onset, serum creatinine and body mass index. Conclusions: Serum CK levels of ALS patients were correlated with sex, site of onsite, serum creatinine and spontaneous activity in electromyography. Serum CK could be an independent prognostic factor for survival of ALS patients.